Relationships between entry skill and 15m time in competitive swimming start - Kazumasa, O.; Shinji, S.; Masahiro, T. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: The purpose of this study was to examine the relationships between skill in entry phase and the glide speed. METHODS: Fourteen collegiate elite male swimmers performed maximal efforts competitiv swimming start followed by 25m freestyle swim. The mean value of the swimmer elapsed time at 15m was 6.81±0.17 sec. The motions above and under water were recorded by synchronized two high speed video cameras (250 fps), and two CCD video cameras (60fps), respectively. The two-dimensional analysis was used to calculate the kinematic variables, such as entry speed, angle of projection, attitude angle and angle of attack. These angles were calculated about entry and glide phase. And, also acceleration in glide phase and angular variation about angle of projection, attitude angle and angle of attack during entry phase were calculated. A correlation analysis was conducted to examine the relationships between performance of start phase (15m time) and the kinematic variables. RESULTS: About kinematic variables in entry phase, angle of projection was 34.4±2.9deg. Attitude angle was 39.5±4.9deg. Angle of attack was -4.6±6.5deg. About kinematic variables in glide phase, angle of projection was 31.0±3.0deg Attitude angle was 11.1±5.8deg. Angle of attack was 19.9±3.8deg.There was a significant negative correlation between 0-15m time and angle of attack (p<0.05; r=-0.534). Also, there was a significant positive correlation between 15m time and acceleration in entry phase (p<0.05 r=0.593). Also, there was a significant negative correlation between angle of attack and acceleration in entry phase (p<0.05 r=-0.599). There was no correlation between angular variation about angle of attack and acceleration in entry phase (p=0.158 r=-0.277). DISCUSSION: The result of this study showed that the angle of attack and acceleration in entry phase influence 15m time. From these result, it is consider that the entry skill explained by angle of attack influence acceleration in entry phase, and therefore 15m time is shorten. But there was no correlation between angular variation about angle of attack and acceleration in entry phase. These results suggest that angular variation about angle of attack do not influence deceleration during entry phase in expert competitive swimmers.